Coastal Shipping Radar Monitoring System with Satellites as Transmitters of Opportunity - Van Quan Nguyen (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. With the development of technology and science, passive radar systems operating on the basis of third-party transmitters of illumination signal sources are increasingly attracting research interest. The use of satellite systems as transmitters of opportunity for a radar station makes it possible to monitor coastal sea areas, where the ground sources of illumination signals are absent. Satellite systems can cover any point on the Earth's surface. Passive radar systems can be used to determine the location of ships and monitor navigation. They are also promising as part of vessel traffic control systems.Aim. To develop a model of a passive radar system that uses satellite systems as third-party sources of illumination signals and to conduct an experimental study of a system for monitoring ships in coastal waters.Materials and methods. The AA2-KKС antennas of satellite signals and radio recording tools based on the universal USRP B210 board were used. Signal processing was performed using a program developed in the MATLAB environment.Results. An algorithm for processing satellite signals of the GPS global navigation system in a passive radar system is proposed. An experimental model of the receiving station for such a radar monitoring system was created on the basis of a data input device for a universal USRP board of the B210 series. Experimental results for the receiving station using the satellite signal GPS L1 C/A-code for coastal monitoring were obtained.Conclusion. The developed experimental model of a passive radar receiving station using third-party transmitters of GPS satellitebased illumination signals on the L1 frequency range of the C/A-code type can be used for detecting ships and monitoring coastal navigation. Future research will consider a multiposition modification of such a monitoring system for improving its detection quality and increasing its target positioning accuracy.